Faktor-faktor yang menghalang kepada keberkesanan pengurusan aduan di Hotel Johor Bahru - Wong, Hie Na (2010)
Complaint management plays a special role in the management of customer retention and customer relationship management (CRM). CRM becomes a necessity strategic for the hotel industry to attract, enhance customer satisfaction and loyalty, and increase the number of repatronage customers. The increase of the hotel industry performance through effective complaints handling is a great challenge as the hospitality industry is constrained by its unique characteristics such as fragmented nature of hotel offering, the nature of post-complaint customer behavior, dissatisfactory service recovery efforts, and so forth. Thus, the study was conducted to identify the factors that hinder the effectiveness of complaint management in the hotel Johor Bahru. Checklist approach and interviews was used to collect data for this study. A total of 17 hotels which comprising of three star hotels, four star hotels and five stars hotels in Johor Bahru have been selected as respondents in this study. At the final stage of data collection, there are 7 hotels have been received an invitation and interview was held with the hotel management people at the hotel respectively. Data analysis methods such as frequency analysis, networks, and content analysis were used in this study. The study found 5 problems encountered by the hotel management at Johor Bahru in the implementation of complaint management which are poor complaint management policy, human resource issues, cost issues in the complaint management, perception of hotel management regard complaint management, and lack of preventive management. Finally, recommendations are also given to the hotel management people regarding the effective ways of complaints handling to improve service quality, customer satisfaction and the most important making a profit.